Pretreatment and Enzymatic Hydrolysis from Water Hyacinth (Eichhornia crassipes) - Jongmeesuk*, Atcharaporn; Sanguanchaipaiwong, Vorapat; Ochaikul, Duangjai (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Water hyacinth (Eichhornia crassipes) is a noxious aquatic weed which grows fast and is a lignocellulosic material containing cellulose, hemicellulose and lignin. It can be utilized to produce reducing sugar for bioethanol production. This research studied a production of reducing sugar from water hyacinth using physical combined with chemical method. The water hyacinth was milled and dried at 105 °C for 5-6 h, then pretreated with acid (sulfuric acid 2.0, 2.5 and 3.0 % v/v) and alkali (sodium hydroxide 2.0, 2.5 and 3.0 % w/v). After heating in an autoclave at 121°C for 15 min, it was found that using 2.0 % v/v sulfuric acid and 2.0 % w/v sodium hydroxide providing the highest reducing sugar of 15.63 and 2.35 g/L, respectively. Therefore, the sulfuric acid concentration of 2.0 % v/v was the most suitable concentration for pretreated water hyacinth. In addition, enzyme loading and time were studied for the optimization of reducing sugar production. The water hyacinth hydrolysate (sludge) was hydrolyzed with ACCELLERASE1500. The result showed that ACCELLERASE1500 loading at 0.30 ml/g water hyacinth and incubated at 50°C for 48 h produced reducing sugar of 11.95 g/L. This is a first report on enzymatic hydrolysis of water hyacinth by ACCELLERASE1500. Keywords: water hyacinth, pretreatment, enzymatic hydrolysis *Corresponding author: kodaungj@kmitl.ac.th, gwang_at@hotmail.com